Marketing Strategies through Product Awareness, Service Quality and Product Quality Assurance on Consumer Purchasing Decisions - Nurbianto, Amanda Threesya; Christian, Timotius Febry (Green Publisher Indonesia, 2024)
In the dynamic pharmaceutical industry, companies are undergoing significant transformations in their interactions with consumers. The health industry involves various stakeholders, and pharmaceutical products, such as medications, are predicted to continually increase in demand with the growth of the middle class in Indonesia. Pharmaceutical manufacturers compete through distribution channels such as pharmacies and large pharmaceutical retailers to meet the demands of the government, patients, and entrepreneurs. With the rising number of patients, PT. Satoria Aneka Industri needs to develop a marketing strategy to remain competitive by enhancing the quality of products, services, and quality assurance. Positioned as the second-largest market share holder, PT. Satoria Aneka Industri aims to become the leader in the Indonesian market with a marketing strategy focused on the Unique Selling Point (USP), improving service quality, and ensuring product quality. Product awareness, service quality, and product quality assurance are considered determining factors in consumer purchasing decisions, with marketing strategy analysis focused on the company's infusion products.